Analisis e interpretacion de los estados financieros a la empresa de transportes Gualaquiza c.a. de la ciudad de Gualaquiza, Provincia de Morona Santiago, periodo 2014-2015. - Tirado Guerrero, Karla Patricia (2017)
The present thesis work allowed to fulfill the financial study carried out by the Gualaquiza Transport Company C.A. being a very significant contribution for the company. Also with the purpose of complying with one of the requirements established in the Academic Regulations, prior to opting for the degree of Accounting and Auditing Engineer, Public Accountant Auditor. In order to comply with the proposed objectives, the investigative work was initiated by conducting an interview with the executives of the company, gathering all the necessary and reliable information, as well as verifying the Financial Statements for the 2014 and 2015 periods, and in turn applying the procedures of the Financial Analysis such as: Vertical Analysis, Horizontal Analysis and Financial Indicators, seeking to determine the liquidity, indebtedness and profitability with which the company has. Finally, a Financial Analysis report was presented containing conclusions and recommendations, as well as improvement alternatives to be followed in the following economic periods. With the completion of the Financial Analysis it was concluded that the company has a high capital of its own and that the profits obtained do not represent a good financial return for it. The report allows the professional to have a valid instrument, for an effective and timely decision making.